2013
DOI: 10.1155/2013/549879
|View full text |Cite
|
Sign up to set email alerts
|

Anacardic Acids from Cashew Nuts Ameliorate Lung Damage Induced byExposureto Diesel Exhaust Particles in Mice

Abstract: Anacardic acids from cashew nut shell liquid, a Brazilian natural substance, have antimicrobial and antioxidant activities and modulate immune responses and angiogenesis. As inflammatory lung diseases have been correlated to environmental pollutants exposure and no reports addressing the effects of dietary supplementation with anacardic acids on lung inflammation in vivo have been evidenced, we investigated the effects of supplementation with anacardic acids in a model of diesel exhaust particle- (DEP-) induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 56 publications
(81 reference statements)
2
16
0
Order By: Relevance
“…***p < 0.001, **p < 0.01, and *p < 0.05 compared with the CFA group (black bar). Sal, saline (0.9 mg/ml); Dex, dexamethasone (5 mg/kg) 2000 mg/kg by the intra-gastric route, since no animal died after administering the samples, and this result is in agreement with the findings of Konan and Bacchi (2007) and Carvalho et al (2013). The information in the short-term and long-term toxic effects of nut oil has already been reported in the literature (Morais et al 2010;Daswanto et al 2016).…”
Section: Discussionsupporting
confidence: 83%
“…***p < 0.001, **p < 0.01, and *p < 0.05 compared with the CFA group (black bar). Sal, saline (0.9 mg/ml); Dex, dexamethasone (5 mg/kg) 2000 mg/kg by the intra-gastric route, since no animal died after administering the samples, and this result is in agreement with the findings of Konan and Bacchi (2007) and Carvalho et al (2013). The information in the short-term and long-term toxic effects of nut oil has already been reported in the literature (Morais et al 2010;Daswanto et al 2016).…”
Section: Discussionsupporting
confidence: 83%
“…The inhibition of the respiration rate shown by 1a is smaller relative to that reported onarachidonic acid [ 54 ], implying that the alkyl side chain has an influence on the uncoupling effect [ 55 ]. It has also been found that oral treatment with anacardic acids improve antioxidant activity of glutathione peroxidase (GPx), glutathione reductase (GR), glutathione S -transferase (GST), and catalase (CAT), enzymes of BALB/c mice lung damaged following exposure of animals to diesel exhaust particulate [ 56 ]. The most effective dose of anacardic acids, 50 mg/kg, decreased levels of neutrophils and tumor necrosis factor (TNF-α) in the lung parenchyma and in the broncho alveolar lavage fluid (BALF) supernatant, respectively [ 56 ].…”
Section: Biological Activity Of Anacardic Acidsmentioning
confidence: 99%
“…Burning fossil fuels is one of the most important sources of particulate material, especially in diesel engines [23]- [26] where its emission is related to the burning of diesel and lubricant oil, besides the bearing and engine materials wear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this option by road mass transport is reaching its limits, because it presents clear signs of saturation, which has been generating serious socio-political crisis in Brazil. The air pollution in large cities is another worrying factor due to the heavy use of road transport, which is seriously impacting population health [23]- [25] [31]- [38].…”
Section: Introductionmentioning
confidence: 99%